Dormancy, activation and viability of Rhizopus oligosporus - Nguyễn, Văn Thành (Wageningen Universiteit, 2004)
Content: introduction; characterization of viability and physiological state transitions of Rhizopus oligosporus; protein profiles of dormant and activated sporangiospores.